2016
DOI: 10.1111/nyas.13150
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal and laryngeal sensory innervation in the pathophysiology of swallowing disorders and sensory stimulation treatments

Abstract: Oropharyngeal dysphagia (OD) affects older and neurological patients, causing malnutrition and dehydration and increasing the risk for aspiration pneumonia. There is evidence that sensory deficits in those populations are closely related to swallowing disorders, and several research groups are developing new therapies based on sensory stimulation of this area. More information on the sensory innervation participating in the swallow response is needed to better understand the pathophysiology of OD and to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 124 publications
(266 reference statements)
1
52
0
Order By: Relevance
“…The literature is ripe with studies exploring the influence of mechanoreceptors, taste receptors, and even thermal receptors on swallowing. Two reviews are dedicated to describing these mechanisms and their evidence . Intuitively, although not obviously, sensory feedback via cranial nerves V, VII, IX, and X is an apt mechanism for the body to know how to best guide a bolus through the digestive tract (Figure , Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature is ripe with studies exploring the influence of mechanoreceptors, taste receptors, and even thermal receptors on swallowing. Two reviews are dedicated to describing these mechanisms and their evidence . Intuitively, although not obviously, sensory feedback via cranial nerves V, VII, IX, and X is an apt mechanism for the body to know how to best guide a bolus through the digestive tract (Figure , Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Older people and patients with neurological diseases suffering from OD present decreased oropharyngeal sensitivity . Reduced sensory input contributes to impaired motor response . Thus, sensory impairment is a potential target for treatment of swallowing dysfunction in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently found that this impaired pharyngeal sensory function is due to disturbances in the pharyngo‐cortical connection together with a disrupted pattern of cortical activation . Studies have also found a close relationship between sensory deficits and impaired swallow response, which might imply that reduced sensory input contributes to impaired motor response . This sensory impairment might be a critical pathophysiological element and a potential target for treatment of swallowing dysfunction in older patients.…”
Section: Introductionmentioning
confidence: 96%
“…More importantly, however, the close relation of SP increase and successful PES treatment alludes to a causal role of SP in the underlying physiological mechanism. SP occurs ubiquitary in the peripheral nervous system, is found in particular in C and Aδ fiber terminals in the pharyngeal mucosa and colocalizes there with TRPV1 channels which have been suggested to play an important role in the perception of noxious stimuli and prevention of aspiration [35, 36]. Thus, it is conceivable that PES triggered release of SP produces peripheral sensitization of sensory neurons, which then facilitates the motor swallow response in the upstream swallowing network.…”
Section: Discussionmentioning
confidence: 99%